COMPARISON OF CONTENT AND LANGUAGE INTEGRATED LEARNING IN THE PRIMARY LEVEL IN SPAIN AND SLOVAKIA - Pavelova, Barbora (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
As many authors agree, positive associations of Content Language Academic Learning have attracted numerous researchers, administrators, teacher educators and teachers, particularly those in the field of English as a foreign language. One of the main goals of the presented article is to offer a comparative analysis of CLIL approach at primary level in Spain and in Slovakia. The need for elaborating this issue is related to the diversity of language and the fact that CLIL has become prolific phenomenon in recent years, especially in pedagogical communication. The paper responds to different claims of the proponents of CLIL emphasizing its numerous benefits. Apart from that, the following paper provides a critical empirical examination of the positive CLIL outcomes in order to identify better its strengths in EFL. Due to distance, a sample of five Spanish teachers and five Slovak teachers at the primary level has been chosen randomly to respond to the online interview elaborating the use of CLIL in the classroom. In order to gain the results of the qualitative nature, the online interview included open-ended questions. Benefits of CLIL could be reflected in the enhanced motivation inside and outside the classroom, the need of students and teachers for critical thinking, requirement for a better concentration and in many other areas. The article presents current findings and brings the possibilities for implementing CLIL into more classrooms and enhancing pedagogical communication in foreign language classrooms.